The Role of Arbitration in Protecting the Financial Rights of Contractors with the Administration: An Application to the Theory of Force Majeure (Comprehensive Journal of Science, 2026)
This study aims to clarify the concept of arbitration in administrative contracts as an alternative means of dispute resolution between the administration and its contractors. It also aims to demonstrate the role of arbitration in protecting the financial rights of contractors and to highlight the role of the arbitration panel in restoring financial balance to administrative contracts by awarding appropriate compensation or modifying contractual obligations in accordance with the principles of justice. This is addressed by the theory of unforeseen circumstances in administrative law. The researcher adopted a descriptive-analytical approach, examining relevant legal writings and opinions, including their points of agreement and disagreement, as well as scientific research and the analysis of legal texts and rulings, in order to gain a comprehensive understanding of all aspects of the study.The study concluded that arbitration is an effective means of settling disputes arising from administrative contracts, due to its speed and flexibility compared to traditional judicial procedures. It also demonstrated that arbitration contributes to protecting the financial rights of contractors by enabling them to claim financial restructuring in the event of exceptional circumstances. The study recommended strengthening the legal provisions governing arbitration in administrative contract disputes to ensure the protection of contractors' financial rights.
Keywords: Arbitration - Protection of Financial Rights - Contracting - Administration - Theory of Force Majeure